The acceptance level of new safety helmet design among palm oil plantation harvesters in Johor, Malaysia - Siti Najihah Abdul Salam,; Shamsul Bahri Md Tamrin,; Dayana Hazwani Mohd Suadi Natab, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Agriculture has the highest number of occupational accident cases reported to the Department of Occupational Safety and Health, Malaysia in 2022. The most serious concern is a head injury, which can lead to serious injury or death. Because of the fundamental issue of discomfort, the current level of safety helmet usage is extremely low. The purpose of this study is to determine the level of acceptance of a new safety helmet design. This single group pre and post-test study were conducted on 124 harvesters in three Johor palm oil plantations by using a modified structured questionnaire. A training session on proper helmet use was conducted via video presentation. For three days, harvesters wore the new safety helmet design. Field observation was conducted on the practice item for the post-test. Descriptive analysis shows harvesters have a high score for knowledge, attitude, and practice. There is no significant difference (p>0.05) in practice before and after the implementation of training. There is a significant increase (p<0.001) in the acceptance level of the parameter (comfort, safety, ventilation, peak, fit, design, and heat) of the new safety helmet design on day 1, day 3 and day 6 among palm oil plantation harvesters. Overall, the harvesters have high knowledge, attitude and practice level and the new safety helmet design is well accepted by the harvesters. Training session implemented is helpful, however, the module needs to be improvised to increase the practice level.